Chitosan nanoparticles functionalized with β-cyclodextrin: A promising carrier for botanical pesticides - Campos, Estefânia V.R. [UNESP]; Proença, Patrícia L.F. [UNESP]; Oliveira, Jhones L. [UNESP]; Melville, Cirano C. [UNESP]; Vechia, Jaqueline F. Della [UNESP]; De Andrade, Daniel J. [UNESP]; Fraceto, Leonardo F. [UNESP] (Springer Nature, 2018)
Carvacrol and linalool are natural compounds extracted from plants and are known for their insecticidal and repellent activities, respectively. However, their low aqueous solubility, high photosensitivity, and high volatility restrict their application in the control of agricultural pests. The encapsulation of volatile compounds can be an effective way of overcoming such problems. Inclusion complexes between beta-cyclodextrin (β-CD) and carvacrol (CVC) or linalool (LNL) were investigated. Inclusion complexes were prepared by the kneading method. Both complexes presented 1:1 host:guest stoichiometry and the highest affinity constants were observed at 20 °C for both molecules. The nanoparticles containing carvacrol and linalool had mean diameters of 175.2 and 245.8 nm, respectively and high encapsulation efficiencies (<90%) were achieved for both compounds. Biological assays with mites (Tetranychus urticae) showed that the nanoparticles possessed repellency, acaricidal, and oviposition activities against this organism. Nanoencapsulated carvacrol and linalool were significantly more effective in terms of acaricidal and oviposition activities, while the unencapsulated compounds showed better repellency activity. The nanoformulations prepared in this study are good candidates for the sustainable and effective use of botanical compounds in agriculture, contributing to the reduction of environmental contamination, as well as promoting the effective control of pests in agriculture.